The effect of Mycoplasma gallisepticum infection on energy metabolism in chicken lungs: Through oxidative stress and inflammation. (January 2020) - Ishfaq, Muhammad; Zhang, Wei; Ali Shah, Syed Waqas; Wu, Zhiyong; Wang, Jian; Ding, Liangjun; Li, Jichang
Abstract: Mycoplasma gallisepticum (Mg) causes chronic respiratory disease (CRD) in chickens. However, the effect of Mg infection on energy metabolism in chicken lungs is still unknown. The present study was aimed to investigate the effect of Mg infection on energy metabolism in chicken lungs. Four-weeks-old white leghorn chickens were randomly divided into control group (L1) and Mg infection group (L2). Histopathology, transmission electron microscopy, qRT-PCR and Western blot were used to determine the hallmarks of ultrastructural analysis, inflammation and energy metabolism. Results revealed that Mg infection induced oxidative stress in the chicken lungs and serum cytokine activities were enhanced at the three time points. Chickens infected with Mg revealed abnormal morphology and cellular damage including increased inflammatory cells infiltrate, cellular debris and exudate, mitochondrial and DNA damage in the lungs. The mRNA and protein expression level of inflammation-related genes were significantly increased in L2 group, showing that Mg induced inflammation in chicken lungs. In addition, ATPase activities were reduced in L2 group compared to L1 group. Meanwhile, the expression of energy metabolism related genes were decreased at both mRNA and protein level at all assessed time points, which showed that Mg infection weakened energy metabolism in chicken lungs. In summary, the data suggested that Mg infection induced oxidative stress, inflammation and energy metabolism dysfunction in the chicken lungs, exploring new therapeutic targets and providing a reference for comparative veterinary medicine. Highlights: The effect of Mg infection on chicken lungs were investigated. Mg-infection causes abnormal morphological changes in chicken lungs. Mg-infection induced oxidative stress, inflammation and energy metabolism dysfunction. The data provide basis for future therapeutic studies to control Mg infection.